“Muy andariega mi hija”: Lesbianism as a path of knowledge in Gloria Anzaldúa - Hernández Piñero, Aránzazu (Millcayac - Revista Digital de Ciencias Sociales, 2025)
In this article, I will address the role played by lesbian existence and experiences in shaping Gloria Anzaldúa’s thought. I will argue that lesbianism constitutes a path of knowledge, where sexual, erotic, epistemological and spiritual dimensions are intertwined. For this, I will interpret the “Coatlicue state” as a description of the consequences of internalized lesbophobia. I will show how Anzaldúa provides clues to understanding the workings of shame as well as the articulation between shame and internalization of dominant ideals. Finally, I will ask how we can change, as we are invited to consider that change is the way.